Evolutionary Knowledge Creation Model Validation Based on Multi Case Study and Simulation - Seyedeh Bahareh Kashian; Abbas Afrazeh; Seyed Mohsen Tabatabaei; Mahmood Biglar (پیاورد سلامت, 2017)
Background and Aim: Modeling of organizational knowledge creation process is one of the key areas of research in knowledge management. The aim of this paper was to determine solutions for developing and improving evolutionary knowledge creation model based on the model validation results in real world. Materials and Methods: This study was an analytical and empirical research that was done by multi case study and simulation strategy. The committee was formed to collect information from various source of data including organizational documents and interview with senior managers about knowledge creation history for 5 years in Development and Planning Management department of Tehran University of Medical Sciences. Data analysis was done using descriptive statistics and qualitative analysis. Also, the mathematical formulation was analyzed using simulation in Excel. Results: In most of analyzed knowledge creation cases, knowledge absorption from external source through changing managers or employing consultant following integration with exist knowledge was occurred. Also, simulation results show that, mathematical relations were not well defined and changing them makes results more acceptable. Conclusion: Knowledge grow in organization has occurred through three ways including planned knowledge creation based on managerial decisions, planned knowledge absorption based on managerial decisions, and random knowledge creation mechanism, and all of them have impact on essential knowledge contents.